Islamic Corporate Governance in the Halal Industry: Sharia Supervisory Board, Sharia Compliance, and Reputational Risk in Sharia Issuers - Aulia, Anggi (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2024)
This study examines the role of Islamic Corporate Governance(ICG)—with a focus on the Sharia Supervisory Board (SSB)—inenhancing sharia compliance and reducing reputational risk insharia-compliant issuers, as well as its implications for investorconfidence. Using a company-year panel design (±2019–2025)across halal sectors (financial and non-financial), the studydevelops two auditable constructs: the Sharia Supervision QualityIndex (IKPS) (SSB competence & independence, meeting intensity,depth of sharia review/audit, follow-up and integration with riskmanagement) and the Substantive Sharia Compliance Index (IKSS)(specificity of contract/material/supplier disclosure, non-halalexposure metrics, supplier assurance, and remediation rate).Reputational risk (REPRISK) is derived from sharia violationevents/news and market indicators, while investor confidence(TRUST) is proxied by the cost of equity capital (COE) and valuation(Tobin's Q/PBV). Estimation is performed using fixed-effects panelregression (firm & year), multilevel mediation test (IKPS → IKSS →REPRISK → TRUST) using bootstrapping, and moderation by halalexposure (HEX); robustness is tested through alternative proxiesand index redefinition. The main results show that IKPS positivelyinfluences IKSS, and IKSS decreases REPRISK. Furthermore, highIKSS and low REPRISK are associated with lower COE and highervaluations, confirming the ICG value channel through complianceand reputation. This effect is stronger in companies with high HEX,indicating the importance of sharia materiality. The researchcontribution lies in the comprehensive and auditable measurementof ICG processes and outcomes, the exploration of step-by-stepmediation mechanisms towards investor trust, and the examinationof heterogeneity of effects based on halal exposure. Practicalimplications emphasize strengthening the capacity andindependence of the SSB, expanding the scope of sharia audits,accelerating the closure of findings, and transparent, metric-baseddisclosures to build credibility of halal reputation and long-termvalue.